2021
DOI: 10.1371/journal.pntd.0009984
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of fungal entomopathogens on survival and immune responses of Aedes albopictus and Culex pipiens mosquitoes in the context of native Wolbachia infections

Abstract: Microbial control of mosquitoes via the use of symbiotic or pathogenic microbes, such as Wolbachia and entomopathogenic fungi, are promising alternatives to synthetic insecticides to tackle the rapid increase in insecticide resistance and vector-borne disease outbreaks. This study evaluated the susceptibility and host responses of two important mosquito vectors, Ae. albopictus and Cx. pipiens, that naturally carry Wolbachia, to infections by entomopathogenic fungi. Our study indicated that while Wolbachia pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Other studies performed on Aedes aegypti mosquitoes showed that the entomopathogenic fungus B. bassiana interacts with the gut microbiota to accelerate mosquito death 37 , and induces a decrease of reactive oxygen species (ROS) activity that result in an increase of the gut microbiota 38 . However, the endosymbiont Wolbachia in Aedes mosquitoes did not provide a protective advantage against entomopathogenic fungal infection 39 . We previously showed that APL1 shapes the enteric bacterial consortium in Anopheles 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies performed on Aedes aegypti mosquitoes showed that the entomopathogenic fungus B. bassiana interacts with the gut microbiota to accelerate mosquito death 37 , and induces a decrease of reactive oxygen species (ROS) activity that result in an increase of the gut microbiota 38 . However, the endosymbiont Wolbachia in Aedes mosquitoes did not provide a protective advantage against entomopathogenic fungal infection 39 . We previously showed that APL1 shapes the enteric bacterial consortium in Anopheles 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, comparatively little attention has been given to the potential for Wolbachia to interact with other types of pathogens, including fungi. Prior research gave contrasting results either suggesting there was a Wolbachia-fungal infection interaction 72,75 or not 71,73,74 . However, these previous studies were performed in different contexts with many different variables between them.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a third study on infection of female spider mites in topical contact with B. bassiana or Metarhizium fungal pathogens indicated that Wolbachia may actually increase mortality of the host with fungal infection 73 . A fourth investigated the effect of Wolbachia on injection with two Beauveria pathogens on Aedes albopictus and Culex pipiens mosquitoes 74 . This study found no enhancement in host survival with the symbiont, but reported some putative differences in host immune gene expression and reduced fungal load in some contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Wolbachia presence did not provide a protective advantage against entomopathogenic fungi, Beauveria bassiana and B . brongniartii , in two important mosquito vectors, Aedes albopictus and Culex pipiens that naturally carry Wolbachia [ 71 ]. Taken together these results plus high microbial loads, we suggest that presence of Wolbachia supergroup F may not provide protection in the German cockroach species.…”
Section: Discussionmentioning
confidence: 99%